Historical Perspective of Athletic Training Clinical Education - Weidner, Thomas G. (attr, 2002)
Objective: To present a historical perspective of the development and evolution of clinical education in the medical and allied health professions, with a special interest in athletic training; to gain a better understanding and appreciation of the depth and breadth of the structured and formal clinical education needed in athletic training, for both the present and the future. Data Sources: Information was drawn from the Educational Resources Information Center (1966–2001), MEDLINE (1966–2001), SPORT Discus (1830–2002), and CINAHL (1982–2002) searches of historical literature relating to the development of medical, allied health, and athletic training clinical education. Key words searched were clinical education, clinical instruction, medical education, allied health education, history of medical education, athletic training education, and history of clerkships. We also used reference materials cited in historical textbooks on medical education. Data Synthesis: Clinical education in American medical schools evolved from a primarily didactic process to the clinical-clerkship model. In contrast, athletic training professional preparation was initially more steeped in clinical experiences and less in didactic instruction. Conclusions/Recommendations: Reviewing medical education over the past century and allied health clinical education over the past 30 years provides interesting insights about the past, present, and future of athletic training professional preparation. Athletic training clinical education is undergoing reform and development, which will subsequently enhance the profession. Athletic training has entered an exciting era in its history.